Dismantling the Hyperconjugation of π‐Conjugated Phosphorus Heterocycles. Issue 38 (11th June 2019) - Larrañaga, Olatz; Romero‐Nieto, Carlos; de Cózar, Abel
Abstract: The development of π‐extended phosphorus heterocycles has been rapidly increasing because of their unique optoelectronics properties, which are very often considered to be a consequence of special hyperconjugative interactions. However, the latter interactions have primarily been investigated within the five‐membered species, phospholes, and they are often conceptually extrapolated to the rest of π‐extended phosphorus heterocycles (including six‐membered P‐heterocycles) despite evident structural differences. Herein, we report, for the first time, a detailed investigation that sheds light on the hyperconjugative effects of a series of phosphorus heterocyclic systems by means of EDA and NBO calculations within a DFT framework. Our results lay the foundations for the future design of π‐extended phosphorus heterocycles with improved optoelectronics properties. Abstract : The development of π‐extended phosphorus heterocycles has been rapidly increasing because of their unique optoelectronics properties, which are very often considered to be a consequence of special hyperconjugative interactions. Herein, a detailed investigation that sheds light on the hyperconjugative effects of a series of phosphorus heterocyclic systems by means of EDA and NBO calculations within a DFT framework is reported (see figure). The results lay the foundations for the future design of π‐extended phosphorus heterocycles with improved optoelectronics properties.